PENGARUH MODAL KERJA DAN TOTAL HUTANG TERHADAP LABA USAHA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK 1NDONESIA PERIODE 2011-2015 - Novien Rialdy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
ABSTRACT--s. Company has used productive working capital to make high profit but themanagement also make loans so that the debt level of the company will increase -.epital that is not always followed by an increase in profit increase. Debt increase isfollowed by an increase in working capital and debt laba.working capital increasefollowed by an increase in profit.-           theories used in this research are those of working capital, debt and working•          capital is a company's investment in short-term assets in the form of cash,inventory and accounts receivable. Debt indicates the source of capital from—  :perating profit is the arithmetic difference between revenues and expenses, not _ comprehensive income-    -e method used is quantitative approach, the kind of research is descriptive, the this research is explanatory. Data collection techniques was performed byn. The populations of this study were Manufacturing Companies listed on the Stock Exchange consisting of 134 companies and the samples consisted of 58:s of the study are significant effect on the working capital operating profit company period 2011-2015 with t.hftuno amounted to 14.196 is bigger 1.97190 ed and Hi accepted. Total debt significant effect on operating profit of the --g company period 2011-2015 with thitung amounted to 6.686 is bigger 1.97190and Hi accepted.of this study is the working capital and total debt significantlyJacturing company operating income in 2011-2015 with the value -of Fmung is —;.s.-ed with the value of Ftabel 3.04 then Fhrtuno > Ftabei means that Ho is rejected ,at=3ceed by the significant value of 0.000 is smaller than 0 05.Working Capital, Debt and Operating Income.